2016
DOI: 10.1037/abn0000119
|View full text |Cite
|
Sign up to set email alerts
|

Older maternal age is associated with depression, anxiety, and stress symptoms in young adult female offspring.

Abstract: The evidence regarding older parental age and incidence of mood disorder symptoms in offspring is limited, and that which exists is mixed. We sought to clarify these relationships by using data from the Western Australian Pregnancy Cohort (Raine) Study. The Raine Study provided comprehensive data from 2,900 pregnancies, resulting in 2,868 live born children. A total of 1,220 participants completed the short form of the Depression Anxiety Stress Scale (DASS-21) at the 20-year cohort follow-up. We used negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
4
25
0
1
Order By: Relevance
“…Our results partially support this hypothesis. The findings that the children of older mothers were at higher risk for internalizing behaviors was consistent with Tearne et al (). Older mothers in Ukraine may feel that they have fewer economic, occupational, and educational opportunities than younger mothers and communicate this sentiment to their children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results partially support this hypothesis. The findings that the children of older mothers were at higher risk for internalizing behaviors was consistent with Tearne et al (). Older mothers in Ukraine may feel that they have fewer economic, occupational, and educational opportunities than younger mothers and communicate this sentiment to their children.…”
Section: Discussionsupporting
confidence: 89%
“…Some researchers have found that children of younger mothers are at higher risk for internalizing problems (Fergusson & Woodward, 1999;Tearne et al, 2015). However, others have not found a relationship between maternal age and child mood disorders (Buizer-Voskamp et al, 2011;McGrath et al, 2014), and some have found that children who were born to older mothers had statistically higher levels of depression, anxiety, and stress in early adulthood than did those born to younger mothers (Tearne et al, 2016).…”
Section: Family and Mother Risk Factors (Microsystem Level)mentioning
confidence: 99%
“…Lack of direction aside, significant interaction effects indicate that cognitive resources play an important role in communication disturbances for patients but not controls, and this occurs above and beyond the influences of state affect. While prior studies have failed to find a significant effect of cognitive load on communication disturbances in chronic schizophrenia and early-stage psychosis (Melinder and Barch, 2003; Minor et al, 2016), the current findings are novel and add to the existing literature on the influential role of cognitive processes on semantically incoherent speech. Several possible explanations warrant mention for the present findings.…”
Section: Discussionmentioning
confidence: 50%
“…Alternatively, mental fatigue might also improve communication coherence. It is highly important to note that these treatment implications are based on preliminary findings and that other investigators have failed to find cognitive reactivity (i.e., a reduction in communication disturbances following cognitive load) in SMI populations (Melinder and Barch, 2003; Minor et al, 2016). Thus, more research on the cognitive mechanisms underlying communication disturbances is needed in order to inform proper treatment implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation